2018
DOI: 10.1021/acs.analchem.8b02523
|View full text |Cite
|
Sign up to set email alerts
|

Truly Immobilization-Free Diffusivity-Mediated Photoelectrochemical Biosensing Strategy for Facile and Highly Sensitive MicroRNA Assay

Abstract: In conventional photoelectrochemical (PEC) analysis, photoactive materials are usually immobilized on electrode surfaces, and such immobilization procedures are tedious and time-consuming, and it is also difficult to prepare electrodes with good reproducibility. To circumvent such limitations, we propose here a truly immobilization-free diffusivity-mediated PEC bionsensing strategy for microRNA assay, using methylene blue (MB) in solution as the photoactive probe, and nonmodified indium tin oxide (ITO) glass a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(60 citation statements)
references
References 41 publications
1
59
0
Order By: Relevance
“…We also investigated the synergistic effect of chemotherapeutic drug and silencing of miRNA-21 for cancer treatment by combining the miRNA-21 antisense strand and Dox into one system. Several studies have reported on oligonucleotide AuNP conjugates for loading of Dox molecules by insertion into GC pairs [34][35][36][37]. Here, oligonucleotide AuNP conjugates were first prepared and then Dox was loaded onto DNA duplexes bound on the oligonucleotide AuNP conjugates.…”
Section: Design and Characterization Of Dox-aunp-probes For Co-delivery Of Antisense Strand Of Mirna-21 And Doxmentioning
confidence: 99%
“…We also investigated the synergistic effect of chemotherapeutic drug and silencing of miRNA-21 for cancer treatment by combining the miRNA-21 antisense strand and Dox into one system. Several studies have reported on oligonucleotide AuNP conjugates for loading of Dox molecules by insertion into GC pairs [34][35][36][37]. Here, oligonucleotide AuNP conjugates were first prepared and then Dox was loaded onto DNA duplexes bound on the oligonucleotide AuNP conjugates.…”
Section: Design and Characterization Of Dox-aunp-probes For Co-delivery Of Antisense Strand Of Mirna-21 And Doxmentioning
confidence: 99%
“…The 3D hollowed out TiO 2 nanowire clusters were rst obtained via Ti mesh anodization because the 3D hollow Ti mesh structure has a low steric hindrance for biological reactions. 21,22 Scanning electron microscopy (SEM) revealed a highly ordered array of nanowire clusters in the synthesized TiO 2 (Fig. 1(a)).…”
Section: Design Guidelines and Microstructure Of The Electrodesmentioning
confidence: 99%
“…Photoelectrochemical (PEC) sensing, as a vibrant electrochemical analytical technology, exhibits striking advantages such as instinctive mechanism and prominent anti-interference for chemical analysis [109]. Notably, PEC analysis involves the conversion of photoactive materials from photo to electricity in which the photo-induced formation of electron-hole pairs in a photoactive material is utilized to initiate oxidation–reduction reactions [110,111]. Therefore, for PEC biosensors, eminent photoactive materials with appropriate band gap, high carrier mobilities, good corrosion resistance, and relatively low cost are critical to performance [109].…”
Section: Signal Transduction and Readout Elementsmentioning
confidence: 99%